Contribution margin and quantity matrix to analyze the product portfolio in the context of SMEs. Criticism of the BCG matrix and its alternatives - Gelmar García-Vidal; Alexander Sánchez-Rodríguez; Reyner Pérez-Campdesuñer; Rodobaldo Martínez-Vivar (Cogent Business & Management, 2023)
AbstractProduct portfolio analysis is a critical aspect of small and medium-sized enterprises (SMEs) strategic planning and decision-making. It helps SMEs assess their existing product offerings, identify areas for improvement, and make well informed decisions about which products to keep, discontinue, or add to their portfolio. This type of analysis is crucial for SMEs as it enables them to optimize their product mix, allocate resources effectively, and respond to market changes, thereby ensuring growth and profitability. The objective of the research is to present a new product portfolio analysis tool that SMEs with a more efficient and effective way of evaluating their product offerings paying attention to those that cause a negative impact on performance. The Contribution Margin and Quantity Matrix (CMQ matrix) enables SMEs to gain a deeper understanding of their product mix, identify areas for improvement, and make informed decisions about which products to keep, discontinue, or add to their portfolio. This can lead to increased efficiency, better resource allocation and increased competitiveness, ultimately contributing to the success and profitability of the SME. The proposed instrument allowed decisions to be made after being applied in the analysis of the product portfolio of a retail store. The application of the proposed matrix allowed the analysis and decision making in relation to the product portfolio of an SME, facilitating an improvement in the performance indicators of the products studied.